CHARACTERISTICS OF CANCER PATIENTS UNDERGOING CHEMOTHERAPY IN MURNI TEGUH HOSPITAL MEDAN - Sitepu, Nunung Febriany; Asrizal; Lufthiani (Caring: Indonesian Journal of Nursing Science, 2019)
Cancer is a group of diseases that occur due to changes in body cells into abnormal cells. Treatment of breast cancer takes a long time and has a negative impact on the physical and mental patients. The cause of patients not following chemotherapy treatment routinely and leaving the chemotherapy treatment schedule in one treatment cycle is because the patient’s physical condition is not strong so he cannot continue treatment. Cancer is one of the leading causes of death in developing countries. Every year the number of cancer sufferers in the world increases to 6.25 million people. In developed countries, cancer is the second leading cause of death after card iovascular diseases.This research is descriptive quantitative research with the aim to analyze the characteristics of cancer patients undergoing chemotherapy in murni teguh hospital medan. The study sample is 30 patient cancer with simple random sampling. . data collection using a questionnaire, consisting of demographic data cancer patients undergoing chemotherapy, collect data in Murni Teguh Hospital Medan, April “ September 2019.